PERTANGGUNGJAWABAN PERDATA PT. MUSTIKA AGUNG SAWIT SEJAHTERA TERHADAP MASYARAKAT DESA BALAI RAJA KABUPATEN BENGKALIS - Simbolon, Veronika YuniAmelia; Lestari, Rika; Hendra, Rahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Civil liability is a legal obligation that requires one party to pay compensation or follow other legalenforcement in a civil action. Company PT. Mustika Agung Sawit Sejahtera, a company founded in Balai RajaVillage, Bengkalis Regency, did not carry out these responsibilities properly and committed Unlawful Acts(PMH) in accordance with what is regulated in the Civil Law. So the research objective of this thesis is todetermine the implementation of PT accountability. Mustika Agung Sawit Sejahtera towards the people ofBalai Raja Village, Bengkalis Regency and to find out the obstacles found by PT. Mustika Agung SawitSejahtera in implementing accountability towards the people of Balai Raja Village, Bengkalis Regency.Theresearch objective of this thesis is to determine the implementation of PT's accountability. Mustika AgungSawit Sejahtera towards the people of Balai Raja Village, Bengkalis Regency and to find out the obstaclesfound by PT. Mustika Agung Sawit Sejahtera in implementing accountability towards the people of Balai RajaVillage, Bengkalis Regency.The research method in this thesis uses a type of sociological legal research, namely research on theeffectiveness of law in society. The nature of this thesis research is descriptive research that systematicallydescribes the facts and characteristics of the object being studied accurately. The data sources used areprimary, secondary and tertiary data sources, data collection techniques in this research are interview,questionnaire and literature review methods, then afterBased on the research results, the first conclusion can be drawn, Implementation of CivilResponsibility by PT. Mustika Agung Sawit Sejahtera in Balai Raja Village, Bengkalis Regency in theEnvironmental Sector has not been implemented optimally, there are still many people in Balai Raja Villagewho have not experienced the program for implementing Corporate Responsibility in the EnvironmentalSector. Second, obstacles in the Implementation of Civil Responsibility by PT. Mustika Agung Sawit Sejahterain Balai Raja Village, Bengkalis Regency in the environmental sector is an obstacle that originates from thecompany's non-compliance with implementing corporate responsibilities and also a lack of understanding ofthe affected communities..